FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI GULA KELAPA (Studi Kasus Indusrti Rumah Tangga Di Desa Sungai Gembar Kecamatan Betara Kabupaten Tanjung Jabung Barat) - Asmaida Asmaida (Universitas Batanghari Jambi, 2009)
The purpose of this research is to investigate the factors that affect the production of coconut sugar (red sugar) in Sungai Gembar village of betara district of West Tanjung Jabung Regency. To collct the data, this research employ survey method. There are two kinds of data: primary data and secondary data. This village is selected on purpose because this village is the center of coconut sugar production. As the sample,There are 35 househods selected by sources. The variables to be measured are raw material (nira). Firewood, workers,and lime.The data collected is analysed by compound linean regression.From the analysis, it is found out that determination coefficient (R2) is 0,998. From the hypothesis testing with F test, it is also found out that F calculated (585,328) > F tabel (2,69). This means that variables of nira, firewood, workers and lime, simultenously, significantly affect the production of coconut sugar. However partial analysis shows that nira and firewood have significant effect on the production : workers and lime do not significantly affect the prodution. The coefficient values of each variable are as fallows : nira 0,777. firewoods 0,260, workers - 0,001, and lime - 0,006. It is seen that nira with 0,777 value are more dominant than the other variables in effecting the production.